IMPLEMENTASI MODEL PEMBELAJARAN BAHASA INGGRIS DI SD DI SURAKARTA - Honest Ummi Kaltsum; Ratnasari Diah Utami (Universitas Muhammadiyah Semarang, 2015)
This research aims to investigate the English learning model applied in elementary school in Surakarta. The population of this research is elementary schools in Surakarta and four elementary schools act as a sample. This research applies qualitative approaches using interview, observation, and documentation to obtain the data. The findings show that elementary schools in Surakarta apply one of the KTSP Curriculum and 2013 Curriculum. Those who apply 2013 Curriculum, consider English as a local content and those which apply KTSP Curriculum, consider English as an extra curricula. In the teaching learning process, the teachers have applied several strategies like lecturing, discussion, and game. The learning sources used to teach is taken from many sources such as textbook, worksheet, and from the internet. There are a little bit obstacles in the teaching learning process such as the varieties of motivation, enthusiastic, and ability of the students. In the learning process, the students want to have varieties approach such as learning in the class, outing class, and using a story. Based on the information above, it can be concluded that English still become one subject in Surakarta elementary school and these school place English either as extra curricula or local content.Keywords: English subject, elementary school, English learning model.